IMPROVING THE EFFICIENCY OF THE DUAL MODEL - Khodjaev , Nodir (MMIT Proceedings, 2023)
The article deals with increasing the effectiveness of the dual model of education by organizing a monitoring and marketing research department in an educational institution.